The Urgency of the Merdeka Learning Curriculum in Improving the Quality of Learning in Schools - Muhammad Zaenul Lael; Na'imah Na'imah; Mahsur Mahsur (Edumaspul: Jurnal Pendidikan, 2024)
The Independent Learning Curriculum is designed with the aim of increasing students' independence and courage in the learning process, while providing greater flexibility for educators to develop learning methods that suit students' individual needs. Through the implementation of the Independent Learning Curriculum, each school is given the authority to choose learning materials and evaluation systems that suit the characteristics and special needs of students in their environment. The aim of this research is to investigate the urgency of the Merdeka Learning curriculum in improving the quality of learning in schools. Thus, it is hoped that this research can become a source of insight and knowledge for the community. The method used in this writing is a qualitative descriptive method with a library research approach. This approach involves collecting information from relevant scientific papers such as books, journal articles, the internet, and other writings related to literature reviews. The results of this research show that learning in the curriculum structure is divided into two main learning activities, namely regular learning or what is usually called intracurricular, and Project Learning for Strengthening the Pancasila Student Profile.